Effect of land use, season, and soil depth on soil microbial biomass carbon of Eastern Himalayas - Nima Tshering Lepcha; N. Bijayalaxmi Devi (Ecological Processes, 2020)
Abstract Background Soil microbial biomass, an important nutrient pool for ecosystem nutrient cycling is affected by several factors including climate, edaphic, and land-use change. Himalayan soils are young and unstable and prone to erosion and degradation due to its topography, bioclimatic conditions and anthropogenic activities such as frequent land-use change. Through this study, we tried to assess how soil parameters and microbial biomass carbon (MBC) of Eastern Himalayan soils originated from gneissic rock change with land-use type, soil depth and season. Chloroform fumigation extraction method was employed to determine MBC from different land-use types. Results Soil physical and chemical properties varied significantly with season, land-use and soil depth (p < 0.001). The maximum values of soil properties were observed in the rainy season followed by summer and winter season in all the study sites. Annual mean microbial biomass carbon was highest in the forest (455.03 μg g− 1 ) followed by cardamom agroforestry (392.86 μg g− 1) and paddy cropland (317.47 μg g− 1). Microbial biomass carbon exhibited strong significant seasonal difference (p < 0.001) in all the land-use types with a peak value in the rainy season (forest-592.78 μg g− 1; agroforestry- 499.84 μg g− 1 and cropland- 365.21 μg g− 1) and lowest in the winter season (forest − 338.46 μg g− 1; agroforestry – 320.28 μg g− 1 and cropland − 265.70 μg g− 1). The value of microbial biomass carbon decreased significantly with soil depth (p < 0.001) but showed an insignificant increase in the second year which corresponds to a change in rainfall pattern. Besides, land-use type, season and soil depth, soil properties also strongly influenced microbial biomass carbon (p < 0.001). Microbial quotient was highest in the agroforestry system (2.16%) and least in the subtropical forest (1.91%). Conclusions Our results indicate that land-use, soil depth and season significantly influenced soil properties and microbial biomass carbon. The physical and chemical properties of soil and MBC exhibit strong seasonality while the type of land-use influenced the microbial activity and biomass of different soil layers in the study sites. Higher soil organic carbon content in cardamom agroforestry and forest in the present study indicates that restoration of the litter layer through retrogressive land-use change accelerates microbial C immobilization which further helps in the maintenance of soil fertility and soil organic carbon sequestration.